2018
DOI: 10.1002/ptr.6089
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroleucodine inhibits mitotic clonal expansion during adipogenesis through cell cycle arrest

Abstract: Aberrant levels of preadipocyte differentiation, triggered by adipocyte hyperplasia and hypertrophy, results in the obesogenic phenotype. Obesity is a risk factor for several metabolic disorders. In this paper, dehydroleucodine inhibited the accumulation of lipid droplets and decreased the elevations of triglycerides, and this inhibitory effect occurred during the early stage of adipogenesis. Thus, not only did dehydroleucodine downregulate the expression of C/EBPα and PPARγ, it also strongly blocked the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Additionally, IAE inhibited the expression of C/EBP-β and the activation of STAT3. Consistent with preceding results, previous studies have reported that plant extracts and their phytochemicals inhibit adipogenesis and lipid accumulation through suppression of MCE, which was dependent on the regulation of cell cycle progression and/or suppression of transcription factors [ 50 , 51 , 52 ]. For instance, Gleditsia sinensis fruit extract suppressed MCE and adipogenesis through the inhibition of p27 KIP1 degradation and the activation of STAT3 [ 7 ].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, IAE inhibited the expression of C/EBP-β and the activation of STAT3. Consistent with preceding results, previous studies have reported that plant extracts and their phytochemicals inhibit adipogenesis and lipid accumulation through suppression of MCE, which was dependent on the regulation of cell cycle progression and/or suppression of transcription factors [ 50 , 51 , 52 ]. For instance, Gleditsia sinensis fruit extract suppressed MCE and adipogenesis through the inhibition of p27 KIP1 degradation and the activation of STAT3 [ 7 ].…”
Section: Discussionsupporting
confidence: 89%
“…These could be one of the mechanisms for puerarin to protect against HFHSinduced liver steatosis. PI3K/AKT signaling pathway is one of the most critical regulatory elements that modulate lipid metabolism (Abood, Veisaga, Lopez, & Barbieri, 2018;Huang et al, 2014). PI3K/AKT activation process could inhibit lipogenesis, retard excessive lipid deposition, and alleviate hepatic steatosis (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Given the association between cell-cycle arrest and adipogenesis, Table 1 shows the effects of phytochemicals on the cell cycle, cell-cycle regulators, and lipid accumulation. Delphinidin, a major anthocyanin widely found in pigmented fruits and vegetables [97]; apigenin, isolated from the flavonoid-rich fraction of Daphne genkwa Siebold et Zuccarini crude extracts [98]; sinigrin, a glucosinolate [99]; curcumin, derived from an Asian spice herb, Curcuma longa , and curcumin-modified forms, bisdemethyoxy-curcumin and curcumin-3,4-dichloro phenyl pyrazole [100,101,102]; dehydroleucodine, isolated from the aerial parts of Artemisia douglasiana [103]; sulforaphane, a naturally occurring isothiocyanate compound, produced in cruciferous vegetables such as broccoli and cabbage [67]; vitisin A, a resveratrol tetramer plentiful in the stembark of Vitis [104]; ellagic acid, present in raspberries, strawberries, walnuts, and pomegranate [105]; and oleuropein and hydroxytrosol, phenolic compounds [106] significantly inhibit intracellular lipid accumulation by increasing the cell population in the G0/G1 phase. Cell-cycle-arrested preadipocytes in the G1 phase of the cell cycle are associated with CDK inhibitory proteins, such as p21 CIP and p27 KIP1 , and Rb phosphorylation [24].…”
Section: Regulation Of Adipogenesis By Various Phytochemicalsmentioning
confidence: 99%
“…Cell-cycle-arrested preadipocytes in the G1 phase of the cell cycle are associated with CDK inhibitory proteins, such as p21 CIP and p27 KIP1 , and Rb phosphorylation [24]. Indeed, delphinidin, dehydroleucodine, bisdemethyoxy-curcumin, curcumin-3,4-dichloro phenyl pyrazole, apigenin, sinigrin, sulforaphane, and vitisin A upregulate p21 CIP and/or p27 KIP1 expression [67,97,98,99,102,103,104,107]. With the concomitant increase of cell number in the G0/G1 phase, decreased phosphorylation of Rb is observed in sulforaphane-, vitisin A-, or ellagic acid-treated cells [67,104,105].…”
Section: Regulation Of Adipogenesis By Various Phytochemicalsmentioning
confidence: 99%